Optimal integration of electric vehicles in smart grids with renewables and battery storage systems under uncertainty - Erfan Mohagheghi; Joan Gubianes Gasso; Pu Li (Trends in Computer Science and Information Technology - Peertechz Publications, 2020)
There has been a huge trend to integrate Renewable Energies (REs) and Electric Vehicles (EVs) into energy networks (Figure 1). This is mostly due to the shrinking price of their application and the increasingly strict emission policy. However, the integration of REs and EVs brings new challenges to the network operation [1]. For instance, a considerable amount of REs cannot be accommodated in the network and thus has to be curtailed due to technical limitations [2-5]. For overcoming this problem, Battery Storage Systems (BSSs) can be used to store the surplus energy and consequently increase economic benefits [4].